Investigating the Mechanistic Target of Rapamycin and Analogous Pathways in Cardiovascular Diseases to Augment Cardiac Functionality - Lewis, Cheryl Rhea (Jordan Journal of Pharmaceutical Sciences, 2025)
Cardiovascular diseases (CVDs) are the leading cause of global mortality, especially in low- to middle-income countries, with heart failure accounting for 34% of deaths, totaling 62.5 million premature deaths in the past decade. Despite initial improvements in survival rates, mortality due to heart failure remains concerning, indicating a decline in the heart’s compensatory capacity as age advances. To understand the molecular complexities of CVDs, this narrative review extensively explored databases such as Scopus, Web of Science, and PubMed using specific inclusion criteria to select articles from experimental studies, clinical trials, animal studies, and observational studies published after the year 2000. Conversely, exclusion criteria were applied to omit articles irrelevant to the topic or published before 2000. The extensive literature search revealed, surprisingly, the largely unexplored potential of targeting the mTOR pathway for the treatment of CVDs. Previous studies suggest that mTOR modulation could reshape cardiac disease pathways, though clinical evidence remains limited. Recent findings underscore mTOR dysregulation in cardiac diseases and show promise in mitigating dysfunction through mTOR inhibition, despite challenges in clinical translation. Understanding mTOR’s crosstalk with other pathways illuminates the complexity of cardiac disease. This review emphasizes mTOR’s significance in coronary artery disease (CAD) and ischemic heart disease (IHD), suggesting avenues for further research and clinical applications to improve cardiovascular disease management and reduce heart failure-related mortality.